The Social Contract - Phase 2, 1976 (London, 1976)
1976 1974-79 "The Social Contract - Phase 2, 1976" [BW0102], 1976, Trades Union Congress The origins of the 'Social Contract' lay in a statement published by the TUC - Labour Party Liaison Committee in February 1973. In 1974, the TUC extended the Social Contract with the new Labour Government for a voluntary incomes policy to combat inflation. Phase 2 of the policy, agreed in May 1976, limited pay rises to £2.50 to £4 per week. The details of the pay guidelines agreed with the Government are set out in this report of the Special Trades Union Congress, held in June 1976.